2021
DOI: 10.3168/jds.2020-19647
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of effects of inoculation with Lactobacillus buchneri, with or without other bacteria, on silage fermentation, aerobic stability, and performance of dairy cows

Abstract: A meta-analysis of 158 peer-reviewed articles was conducted to examine effects of inoculation with Lactobacillus buchneri (LB)-based inoculants (LBB) that did or did not include homolactic or obligate heterolactic bacteria on silage fermentation and aerobic stability. A complementary meta-analysis of 12 articles examined LBB inoculation effects on dairy cow performance. Raw mean differences between inoculant and control treatment means weighted by inverse variance were compared with a hierarchical effects mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 59 publications
5
27
0
Order By: Relevance
“…Although there are a range of inoculants based on L. buchneri available on the market, recent studies testing different strains as silage inoculants on a variety of forages in tropical regions are still inconsistent [10][11][12]. Indeed, in a recent meta-analysis, Arriola et al [13] concluded that silage inoculation with L. buchneri increased aerobic stability of all silages except tropical grasses. Thus, more research is needed on the use of new microorganisms, especially those isolated under tropical conditions with antimicrobial activity that may result in significant effects on fermentation parameters and aerobic deterioration, and, consequently, improvements in silage quality.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a range of inoculants based on L. buchneri available on the market, recent studies testing different strains as silage inoculants on a variety of forages in tropical regions are still inconsistent [10][11][12]. Indeed, in a recent meta-analysis, Arriola et al [13] concluded that silage inoculation with L. buchneri increased aerobic stability of all silages except tropical grasses. Thus, more research is needed on the use of new microorganisms, especially those isolated under tropical conditions with antimicrobial activity that may result in significant effects on fermentation parameters and aerobic deterioration, and, consequently, improvements in silage quality.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, inoculation of L. plantarum enhanced the LA production and decreased the pH rapidly in the early stage of ensiling. A recent meta-analysis concluded that inoculation with L. buchneri increased the concentration of acetate, reduced yeast counts and improved aerobic stability (Arriola et al 2021). However, the effects of LAB inoculation on ensiling different raw materials are not necessarily similar.…”
Section: Discussionmentioning
confidence: 99%
“…Though dual purpose inoculants are attractive (Arriola et al, 2021), there is significant variation in microbial efficiency even within the same plant material. In the present study, maize and lucerne silages were selected due to their importance for the local economy.…”
Section: Discussionmentioning
confidence: 99%